PENGARUH DISIPLIN TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN PROVINSI JAMBI - Lili Andriani, Viktori Rahman (Universitas Batanghari Jambi, 2018)
Abstract This study aims to determine the description of respondents and the influence of discipline on the performance of employees at the Department of Transportation Jambi Province. Based on data analysis on the results of research that there is a significant influence between the discipline on the performance of employees at the Department of Transportation Jambi Province. From the results of analysis that has been done through the use of SPSS 19 software, especially in the correlation table shown that the influence of disciplinary variables on the performance of employees of the Department of Transportation Jambi Province is equal to 2.811 or 28%. Whether this influence is significant or not can also be seen from a significant number of 0.000 which is much smaller than the alpha number of 5%. That is, the discipline has a positive effect on the performance of employees of Jambi Provincial Transportation Department. Keyword : Discipline, Employee Performance.